Extended Neuroendoscopic Endonasal Approach for Resection of Craniopharyngioma in Children - Wu, Danyang; Xu, Ling; Xie, Sungel; Sun, Feiji; Xie, Mingxiang; Wang, Pei; Xiao, Shunwu (Frontiers in Neurology, 2022)
Objective: To explore the surgical approach and technique of neuroendoscopic endonasal resection of pediatric craniopharyngiomas, and to further evaluate its safety and effect in in children. Methods: The clinical data of 8 children who with craniopharyngiomas were surgically treated by neuroendoscopy through extended endonasal approach in our center from 2018 to 2021 were retrospectively analyzed. The related surgical approach and technique were evaluated to improve the surgical results and further reduce the surgical complications when removing craniopharyngioma in children. Results: All 8 patients achieved a gross-total resection of tumor under neuroendoscopy. Postoperatively, 2 cases of transient hyperthermia and 4 cases of transient hyper- and/or hyponatremia occurred within the first two weeks, all of which were quickly controlled. Seven patients had symptoms of diabetes insipidus to varying degrees after the operation, and 4 of them improved within 1-3 months after surgery, but 3 cases still needed oral pituitrin. There were no cases of coma or death, leakage of cerebrospinal fluid (CSF), and severe electrolyte imbalance after surgery. During the postoperative follow-up of 3 months to 2 years, no tumor recurrence was found. Among the 7 patients who suffered postoperative neuroendocrine deficiencies, 3 patients were found to be temporary during the follow-up, but 3 patients still required hormone replacement therapy. Particularly, postoperative visual deterioration and olfactory defect occurred in patients were all improved during follow-up periods. In addition, 4 cases of obesity were noted at last follow-up. Conclusions: Extended neuroendoscopic endonasal resection of craniopharyngiomas may be as a safe and effective approach for children. Due to the poor pneumatization of the sphenoid sinus and worse compliance of treatment in children, surgical techniques of exposing the sellar region, removing tumor and reconstructing skull base, as well as postoperative patients’ managements, were proposed. However, due to the limited surgical cases in the study, the surgical safety and effects of the extended neuroendoscopic endonasal approach for children with craniopharyngiomas need to be further studied in the future.